Driving following a diagnosis of dementia: Exploring the views and experiences of people with dementia—A UK survey. (3rd February 2023) - Gouldsborough, Victoria; Fairmichael, Fergus; Davison, Christopher; Hetherington, Victoria; Barber, Robert
Abstract: Background: Driving cessation can be one of the adjustments made following a diagnosis of dementia. Little is known about the views and opinions of people living with dementia about this. The study aimed to gather a broad idea of the expectations, impacts and the process of driving cessation from the perspective of those living with dementia. Methods: 138 people with dementia and 91 relatives/friends (on behalf of an individual with dementia) took part in an online questionnaire. Results: People living with dementia reported stopping driving following diagnosis can have negative psychological impacts particularly in relation to; feelings of isolation, depression, loss of freedom and feeling life isn't worth living. Age, gender and choice in the driving cessation process were related to the degree of negative experiences. Conclusions: The difficulties reported by people with dementia suggest a need to provide more structured post diagnostic support to aid decision making of driving continuation or cessation; with the view to reducing associated distress and enabling people with dementia to continue to live a meaningful life. Key points: Stopping driving following a diagnosis of dementia can have significant negative psychological impacts on the person with dementia. Male gender, young age and being unable to work increases the risk of negative psychological impacts. Supporting people with dementia to make their own informed decisions may help the adjustment process to stopping driving. Post diagnostic support should include support for those affected by stopping driving. Driving assessments were found to be supportive. It is essential these remain available as a means to support safe decision‐making surrounding continuing or stopping driving.